Performance of cs-sleeve under direct tensile load: part 1: failure modes - Ling, Jen Hua; Abd. Rahman, Ahmad Baharuddin; Mirasa, Abdul Karim; Abd. Hamid, Zuhairi (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2008)

(untitled)
Tensile resistance of a sleeve connector used to connect between two structural components by confining grouted reinforcement bars relies on the bond interaction among reinforcement bars, sleeve and grout. Slippage of the reinforcement bars is customary cause of damage in end-to-end grout-filled reinforcement connector under direct tensile force. In this study, a total of nine specimens with different configuration, in terms of sleeve lengths, sizes, configurations, rebar surface conditions and grouting material, were subjected to tensile test. This paper presents the result obtained from tests conducted on the proposed CS-Series specimens and discusses the failure mode as well as the mechanisms that governed the tensile resistance of the specimens. The test data indicates that threads on reinforcement bar had significantly deteriorated the bonding mechanism between reinforcement bars and grout. None of the specimens could achieve the required strength. However, the understandings of the causes of failures obtained from the study provided essential basis for future research.